Penerapan Metode Sosiodrama untuk Meningkatkan Minat Belajar Siswa pada Pembelajaran Sejarah - Sari Oktarina (FKIP ULM, 2021)
Research has been carried out on applying the sociodrama method to increase students' interest in history learning. This research was conducted in two cycles, each cycle implemented in two meetings. The subjects in this study were students of class XI IPS 3 consisting of 36 people in total. This study used techniques in the data collection process: observation, interviews, questionnaires, documents and evaluation results to strengthen research results. The results of Classroom Action Research in the application of the sociodrama method have shown that learning activities took place very satisfactorily. Students were more active and enthusiastic in learning implementation, and teachers acted as motivators and facilitators. Three important points to measure the success of learning: First, the results of sociodrama learning activities achieved a classical increase from cycle I to cycle II, listening activities increased by 28%, sociodrama increased by 36%, discussion or criticism increased by 55%, and evaluation activities increased by 47%. Second, the results of the evaluation activities from Cycle I to Cycle II have increased by 47%. Third, student responses to the questionnaire on the interest in learning History obtained an average percentage of students of 36% in the agreeing category and 64% strongly agree. Thus, it can be concluded that the application of the Sociodrama method has succeeded in increasing student interest in learning history in class XI IPS 3 at SMA Negeri 5 Banjarmasin.Keywords: History Learning; Learning Interest; Sociodrama MethodPenelitian telah dilakukan tentang penerapan metode sosiodrama untuk meningkatkan minat belajar siswa pada pembelajaran Sejarah. Pendekatan dalam penelitian ini menggunakan Classroom Action Research yang dilakukan dalam dua siklus, masing-masing siklus dilaksanakan untuk dua kali pertemuan. Subyek dalam penelitian ini adalah siswa kelas XI IPS 3 berjumlah 36 orang. Penelitian ini menggunakan teknik dalam proses pengumpulan data: observasi, wawancara, angket, dokumen, dan hasil evaluasi untuk memperkuat hasil penelitian. Hasil Penelitian Tindakan Kelas dalam penerapan metode sosiodrama telah menunjukan kegiatan pembelajaran berlangsung dengan sangat memuaskan. Siswa lebih aktif dan antusias dalam melaksanakan pembelajaran dan guru bertindak sebagai motivator dan fasilitator. Tiga poin penting yang menjadi tolak ukur keberhasilan pembelajaran: Pertama, hasil kegiatan pembelajaran sosiodrama, mencapai peningkatan secara klasikal dari siklus I ke siklus II kegiatan mendengar naik 28 %, bersosiodrama naik 36 %, diskusi atau mengkritisi naik 55 % dan kegiatan evaluasi naik 47 %. Kedua, hasil kegiatan evaluasi siklus I ke siklus II mengalami kenaikan 47 %. Ketiga, hasil respon siswa terhadap angket minat belajar Sejarah diperoleh rata rata persentase siswa sebesar 36 % dalam kategori setuju dan sebesar 64 % sangat setuju. Dengan demikian, dapat disimpulkan bahwa penerapan metode sosiodrama telah berhasil meningkatkan minat belajar siswa pada pembelajaran Sejarah kelas XI IPS 3 di SMA Negeri 5 Banjarmasin.Kata Kunci: Metode Sosiodrama; Minat Belajar; Pembelajaran Sejarah